2023
DOI: 10.1007/s40692-023-00264-0
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing learner profiles in a microlearning app for training language learning peer feedback skills

Abstract: Peer feedback can be described as the act of one learner evaluating the performance of another learner. It has been shown to impact student learning and achievement in language learning contexts positively. It is a skill that can be trained, and there have been calls for research on peer feedback training. Mobile microlearning is a type of technology-enhanced learning which is notable for its short duration and flexibility in the time and place of learning. This study aims to evaluate how an asynchronous micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Xiaodong (2022) found that integrating microlearning into a hybrid online and offline learning environment for spoken English contributed to college students' English-speaking proficiency. Moreover, in relation to the improvement of English speaking, Gorham et al (2023) found that the utilization of an asynchronous microlearning app called Pebasco contributed to the development of college students' peer feedback skills regarding spoken English content.…”
Section: Microlearning For English Acquisition and Speaking Abilitiesmentioning
confidence: 99%
“…Xiaodong (2022) found that integrating microlearning into a hybrid online and offline learning environment for spoken English contributed to college students' English-speaking proficiency. Moreover, in relation to the improvement of English speaking, Gorham et al (2023) found that the utilization of an asynchronous microlearning app called Pebasco contributed to the development of college students' peer feedback skills regarding spoken English content.…”
Section: Microlearning For English Acquisition and Speaking Abilitiesmentioning
confidence: 99%
“…In peer evaluation, students provide ratings and feedback on each other's work, which is formative and can promote their performance in subsequent tasks (Gorham et al, 2023;Ohland et al, 2012). Research has shown that peer evaluation encourages students to think deeply and critically about their own work and contributes to the development of "internal feedback" skills, where learners reflect on and regulate their own learning processes (Nicol et al, 2014;To & Panadero, 2019).…”
Section: Peer Evaluation In Team-based Learning (Tbl)mentioning
confidence: 99%
“…Nevertheless, the reliability of unserious peer raters can be improved by proper interventions (Van Zundert et al, 2010). Current studies have made attempts to calibrate scores based on student engagement and previous performance (Piech et al, 2013), afford group awareness information (Strauß & Rummel, 2021), or train evaluation skills during the peer evaluation process (Gorham et al, 2023). These approaches can be too late to nudge timely interventions to the ongoing evaluation activity.…”
Section: Introductionmentioning
confidence: 99%
“…The English vocabulary mobile microlearning system should be gradually applied to colleges and universities. Gorham, Majumdar & Ogata (2023) also evaluated how an asynchronous microlearning app might develop students' skills for providing peer feedback on EFL spoken content. This study adopted a quasi-experimental single-group pre-post-research design.…”
Section: Microlearningmentioning
confidence: 99%